Moderate recovery unnecessary to sustain high stroke volume during interval training. A brief report - Stanley, J.; Buchheit, M. (Journal of Sports Science & Medicine, 2014)
It has been suggested that the time spent at a high stroke volume (SV) is important for improving maximal cardiac function. The aim of this study was to examine the effect of recovery intensity on cardiovascular parameters during a typical high-intensity interval training (HIIT) session in fourteen well-trained cyclists. Oxygen consumption (VO2), heart rate (HR), SV, cardiac output (Qc), and oxygenation of vastus lateralis (TSI) were measured during a HIIT (3×3-min work period, 2 min of recovery) session on two occasions. VO2, HR and Qc were largely higher during moderate-intensity (60%) compared with low-intensity (30%) (VO2, effect size; ES = +2.6; HR, ES = +2.8; Qc, ES = +2.2) and passive (HR, ES = +2.2; Qc, ES = +1.7) recovery. By contrast, there was no clear difference in SV between the three recovery conditions, with the SV during the two active recovery periods not being substantially different than during exercise (60%, ES = -0.1; 30%, ES = -0.2). To conclude, moderate-intensity recovery may not be required to maintain a high SV during HIIT.